Cloning of cDNAs encoding two related 100-kD coated vesicle proteins (alpha-adaptins) (The Rockefeller University Press, 1989)
Coat proteins of approximately 100-kD (adaptins) are components of the adaptor complexes which link clathrin to receptors in coated vesicles. The alpha-adaptins, which are found exclusively in endocytic coated vesicles, separate into two bands on SDS gels, designated A and C (Robinson, M. S., 1987. J. Cell Biol. 104:887-895). Two distinct cDNAs (sequences 1 and 2) encoding the two alpha-adaptins were cloned from a mouse brain cDNA library. Southern blotting indicates that there is one copy of each of the two alpha-adaptin genes, and that there are no additional closely related genes. Based on the size of the predicted protein products of the two genes (108 and 104 kD), the relative abundance of the two messages in brain and liver, and the reactivity of a sequence 1 fusion protein with different antibodies, it was possible to conclude that sequence 1 codes for A and sequence 2 for C. The two protein sequences are strikingly homologous to each other (84% identical amino acids), the major difference being an additional stretch of 41 amino acids, rich in prolines and acidic residues, inserted into the COOH-terminal half of A. In situ hybridization carried out on mouse brain sections indicates that the same cell type may express both transcripts, but that their relative expressions vary. Antipeptide antibodies are now being raised to find out whether the proteins are localized in functionally distinct populations of endocytic coated vesicles.